Maternal obesity trends in a large Irish university hospital. (July 2019) - Reynolds, Ciara M.E.; Egan, Brendan; McMahon, Léan; O'Malley, Eimer G.; Sheehan, Sharon R.; Turner, Michael J.
Abstract: Objective(s): This study aimed to examine recent trends in maternal obesity. Study design: This retrospective observational study used routinely computerised clinical and sociodemographic data of women who presented for antenatal care in a large maternity hospital in Ireland during the eight years 2010-17. Women with complete body mass index (BMI) data who delivered a baby weighing ≥500 g were included in the study. BMI was based on the measurement of weight and height and was categorised into the World Health Organizations (WHO) classifications. Results: The number of women delivered was 67, 949 and 99.1% had complete data. The overall obesity rate increased from 16.0% (95% CI 15.3–16.8%) in 2010 to 18.9% (95% CI 18.0–19.7%) in 2017 (+18.1%, p < 0.001). This increase occurred in the mild, moderate and severe obesity subcategories (all p < 0.01). Overall, obesity was associated with multiparity, maternal age, maternal birth in Ireland or the United Kingdom (UK), depression, unemployment and unplanned pregnancy. The increase in obesity was more pronounced in nulliparas than in multiparas, particularly nulliparas <30 years. The increased obesity levels were accompanied by major sociodemographic changes in the hospital population from 2010 to 2017 with an increase in the average maternal age from 30.5 years to 32.2 years (p < 0.001) and a decrease in the proportion of nulliparas aged <30 years (from 40.6% to 28.8%, p < 0.001). Conclusion(s): It is likely that the escalating maternal obesity levels will lead to further increases in obstetric complications and interventions. The escalation was accompanied by major sociodemographic changes which have implications for healthcare planning and public health interventions.